Answer:
The owner needs to mix 11 pounds of chocolate
Step-by-step explanation:
Let
x ----> the number of pounds of chocolate needed
we know that
The linear equation that represent this problem is equal to
[tex]18.90x+3.30(22)=8.50(x+22)[/tex]
solve for x
[tex]18.90x+72.6=8.50x+187[/tex]
[tex]18.90x-8.50x=187-72.6[/tex]
[tex]10.4x=114.4[/tex]
[tex]x=114.4/10.4[/tex]
[tex]x=11\ pounds[/tex]
a^3b^-2c^-1d if a=2 b=4 c=10 d=15 express as a reduced fraction
[tex]\bf a^3b^{-2}c^{-1}d\implies \cfrac{a^3d}{b^2c}\qquad \begin{cases} a=2\\ b=4\\ c=10\\ d=15 \end{cases}\implies \cfrac{2^3\cdot 15}{4^2\cdot 10}\implies \cfrac{120}{160}\implies \cfrac{3}{4}[/tex]
Find the equation in slope-intercept form that describes a line through (4, –2) with slope –3
Answer:
y = - 3x + 10
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
here slope m = - 3, hence
y = - 3x + c ← is the partial equation
To find c substitute (4, - 2) into the partial equation
- 2 = - 12 + c ⇒ c = - 2 + 12 = 10
y = - 3x + 10 ← equation of line
Answer: [tex]y=-3x+10[/tex]
Step-by-step explanation:
The equation of a line in intercept form: [tex]y=mx+c[/tex]
The equation of a line passing through (a,b) and has slope m is given by :_
[tex](y-b)=m(x-a)[/tex]
Similarly, the equation in slope-intercept form that describes a line through (4, -2) with slope -3 will be :_
[tex](y-(-2))=-3(x-4)\\\\\Rightarrow\ y+2=-3x+12\\\\\Rightarrow\ y=-3x+12-2\\\\\Rightarrow\ y=-3x+10\ \ \text{In intercept form}[/tex]
Hence, the equation in slope-intercept form that describes a line through (4, -2) with slope -3 = [tex]y=-3x+10[/tex]
About 95% of sixth-grade students will have heights between ______ inches and ______inches.
Answer:
53.4 and 62.6
Step-by-step explanation:
Answer:
53.4 and 62.6
Step-by-step explanation:
Got it right :/
Solve: ( Brainliest ) -- TIME LIMIT: 8:00 minutes
2/3·z=10/9
Answer in proper and improper
Answer:
z = 5/3 or 1 2/3
Step-by-step explanation:
2/3·z=10/9
Multiply each side by 3/2
3/2*2/3·z=10/9*3/2
z = 30/18
We can simplify by dividing the top and bottom by 6
z = 5/3
Changing to a mixed number
z =1 2/3
Answer:
1⅔ [OR 5⁄3]
Step-by-step explanation:
2 × ? = 10
---------------
3 × ? = 9
That would be 1⅔.
I am joyous to assist you anytime.
(50 Points)
Drag each description to the correct location on the table. Each description can be used more than once.
Some systems of equations and their graphs are given in the table. For each system, place the description(s) in the box that correctly describe the type of system shown.
Please helppppp :((((
Answer:3x+y=3 is the red line.
6x+y=-4 is the blue line.
Step-by-step explanation:I answer it on the test it is right..
Help!!
Which of the following options is the cheapest per month over all? Assume a month has 30 days
A. rent 11.95 a day
B Lease 149.00 a month 3180 due at signing
C. Buying 16,000.00
D Finance 389.00 /month
Answer:
The correct option is A.
Step-by-step explanation:
We need to find the cheapest per month over all.
Assume a month has 30 days.
In option A:
Rent = 11.95 a day
Monthly rent = 11.95 × 30 = 358.5
Total renting amount is 358.5.
In option B:
Lease = 149.00 a month 3180 due at signing
Total amount = 149 + 3180 = 3329
Total leasing amount is 3329.
In option C:
Buying = 16,000
In option D:
Finance = 389.00 /month
The cheapest amount for a month is 358.5 .Therefore the correct option is A.
Answer: renting a car
Step-by-step explanation:
Lara is a 50% partner. She is guaranteed payment of no less than 20,000. The partnership's income before deducting guaranteed payment is 50,000 what is Lara's distributive share?
Answer:
Lara's share = 25000
Step-by-step explanation:
Partnership's income = 50,000
Lara's guaranteed payment = 20,000
As the Income 50,000 is larger than Lara's guaranteed payment i.e 20,000. Since Lara is 50% partner so she will receive half the amount of the partnership's income.
Partnership's Income = 50,000
Half of Partnership's income = 50,000/2
= 25,000
Therefore, Lara's distributive share is 25,000.
!!
Which is a perfect square?
Answer:
121
Step-by-step explanation:
THIS IS BECAUSE 11*11 = 121
Answer:
121
Step-by-step explanation:
121= 11x11, that is the only option
140 has no square
168 is close, but still isn't a square
195 is 1 away from a square, but not a square
sin y +cos y + tan y sin y = sec y +cos y tan y. Verify the Identity. Show all Steps!
[tex]\bf sin(y)+cos(y)+tan(y)sin(y)=sec(y)+cos(y)tan(y) \\\\[-0.35em] ~\dotfill\\\\ sin(y)+cos(y)+tan(y)sin(y)\implies sin(y)+cos(y)+\cfrac{sin(y)}{cos(y)}\cdot sin(y) \\\\\\ sin(y)+cos(y)+\cfrac{sin^2(y)}{cos(y)}\implies \stackrel{\textit{using the LCD of cos(y)}}{\cfrac{sin(y)cos(y)+cos^2(y)+sin^2(y)}{cos(y)}} \\\\\\ \cfrac{sin(y)cos(y)+\stackrel{cos^2(y)+sin^2(y)}{1}}{cos(y)}\implies \cfrac{sin(y)cos(y)+1}{cos(y)} \\\\\\ \cfrac{sin(y)}{cos(y)}\cdot cos(y)+\cfrac{1}{cos(y)}\implies tan(y)cos(y)+sec(y)[/tex]
Do you guys know the answer for number 4
Answer:
G !!! Have a good day BLOODY
The longer base of an isosceles trapezoid measures 18 ft. The nonparallel sides measure 8 ft, and the base angles measure 75 degrees.
a) Find the length of a diagonal.
b) Find the area.
Answer:
a) The length of the diagonal is 17.71 feet
b) The area of the trapezoid is 123.14 feet²
Step-by-step explanation:
* Lets explain how to solve the problem
- Look to the attached figure
- ABCD is an isosceles trapezoid
∵ DC is the longer base with length 18 feet
∵ AD and BC are the two non-parallel sides with length 8 feet
∵ ∠ ADC and ∠ BCD are the bases angles with measure 75°
- AE and BF are ⊥ DC
# In Δ BFC
∵ m∠BFC = 90° ⇒ BF ⊥ CD
∵ m∠C = 75°
∵ BC = 8
∵ sin∠C = BF/BC
∴ sin(75) = BF/8 ⇒ multiply both sides by 8
∴ BF = 8 × sin(75) = 7.73
∵ cos∠C = CF/BC
∴ cos(75) = CF/8 ⇒ multiply both sides by 8
∴ CF = 8 × cos(75) = 2.07
# In Δ BFD
∵ m∠BFD = 90°
∵ DF = CD - CF
∴ DF = 18 - 2.07 = 15.93
∵ BD = √[(DF)² + (BF)²] ⇒ Pythagoras Theorem
∴ BD = √[(15.93)² + (7.73)²] = 17.71
a)
∵ BD is the diagonal of the trapezoid
* The length of the diagonal is 17.71 feet
b)
- The area of any trapezoid is A = 1/2 (b1 + b2) × h, where b1 and b2
are the barallel bases and h is the height between the two bases
∵ b1 is CD
∴ b1 = 18
∵ b2 is AB
∵ AB = CD - (CF + DE)
∵ ABCD is an isosceles trapezoid
∴ CF = DE
∴ AB = 18 - (2.07 + 2.07) = 13.86
- BF is the perpendicular between AB and CD
∴ BF = h
∴ h = 7.73
∵ A = 1/2 (18 + 13.86) × 7.73 = 123.14
* The area of the trapezoid is 123.14 feet²
can someone help with this question?
Answer:
y ≤ ¼x + 1
Step-by-step explanation:
Starting from the y-intercept of course, use rise\run until you hit another endpoint [finding the rate of change (slope)]. That means me we go up north one block, then go over four blocks east, and since the slope is already simplified, we do not need to go any further. Now all we have left is to determine the correct inequality symbol, and since we know that the bottom portion of the graph is shared, we automatically know it is less than, but to check this, we need to do what is called a zero-interval test [do not recall the actual term], meaning that we plug in 0 for both y and x, getting 0 < 1, which is a GENUINE statement, so the bottom portion stays shaded, otherwise we would have had to shade the top portion if it were a false statement. Finally, we have to determine if we have to add an equivalence line under the inequality symbol, and we DO because as you can see, the line is SOLID BLACK. If it were DASHED BLACK, then it would stay "<" instead of "≤".
I am joyous to assist you anytime.
the area of this rectangle is 4x^2.what does the coefficient 4 mean in terms of the problem?
Answer:
If the width of the rectangle is x than the length is 4x because 4x*x is 4x^2
Step-by-step explanation:
PLEASE HELP!!!
The following table shows a proportional relationship between A and B.
A= 8, 24, 40 B= 3, 9, 15
Write an equation to describe the relationship between A and B.
Answer:
b=3/8a
Step-by-step explanation:
Have a good night/day<3
To find the equation describing the proportional relationship between A and B, we divide B by A and find that the constant of proportionality is 3/8. Thus, the equation is B = (3/8)A.
To find the equation that describes the proportional relationship between A and B, we can start by examining the given pairs of values. For A = 8, B = 3; for A = 24, B = 9; and for A = 40, B = 15. We observe that as A increases, B increases at a constant rate. This suggests a direct proportionality between A and B.
To determine the constant of proportionality (the rate at which B changes with respect to A), we can divide the values of B by the corresponding values of A. Doing so, we find:
B/A for (8, 3) = 3/8B/A for (24, 9) = 9/24B/A for (40, 15) = 15/40All these ratios reduce to 3/8, which is the constant of proportionality. Therefore, B is 3/8 times A, which we can express as:
B = (3/8)A
This equation represents the proportional relationship between A and B, with the constant of proportionality being 3/8.
Which of the following is the equation of a line that passes through (-2,1) and (-4,-3)?
Points [tex]X(-2,1)[/tex] and [tex](-4,-3)[/tex] are defined therefore we have all data we need to construct equation.
Linear function has a form of,
[tex]y=ax+b[/tex]
First calculate the slope a.
[tex]a=\dfrac{dy}{dx}=\dfrac{-3-1}{-4-1}=\dfrac{-4}{-5}=\dfrac{4}{5}[/tex]
Now plug in the coordinates of either one of the points into the linear function. I'll pick point X.
[tex]y=ax+b\Longrightarrow1=\dfrac{4}{5}\cdot(-2)+b[/tex]
Now just solve for b.
[tex]1=-\dfrac{8}{5}+b\Longrightarrow b=\dfrac{13}{5}[/tex]
The equation is therefore,
[tex]\boxed{y=\dfrac{4}{5}x+\dfrac{13}{5}}[/tex]
Hope this helps.
r3t40
a line passes through (3,-2) and (6,2). write an equation in point-slope form. rewrite the equation in standard form
again, bearing in mind that standard form for a linear equation means
• all coefficients must be integers, no fractions
• only the constant on the right-hand-side
• all variables on the left-hand-side, sorted
• "x" must not have a negative coefficient
[tex]\bf (\stackrel{x_1}{3}~,~\stackrel{y_1}{-2})\qquad (\stackrel{x_2}{6}~,~\stackrel{y_2}{2}) \\\\\\ slope = m\implies \cfrac{\stackrel{rise}{ y_2- y_1}}{\stackrel{run}{ x_2- x_1}}\implies \cfrac{2-(-2)}{6-3}\implies \cfrac{2+2}{6-3}\implies \cfrac{4}{3} \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-(-2)=\cfrac{4}{3}(x-3)\implies y+2=\cfrac{4}{3}x-4 \\\\[-0.35em] ~\dotfill[/tex]
[tex]\bf y=\cfrac{4}{3}x-6\implies \stackrel{\textit{multiplying both sides by }\stackrel{LCD}{3}}{3(y)=3\left( \cfrac{4}{3}x-6 \right)}\implies 3y=4x-18 \\\\\\ -4x+3y=-18\implies \stackrel{\textit{standard form}}{4x-3y=18}[/tex]
What does h(40)=1820 mean in terms of the problem ? Help please
Final answer:
The notation h(40)=1820 means that the function h produces an output of 1820 when the input is 40, although additional context is needed to determine what h represents specifically in this scenario.
Explanation:
The expression h(40)=1820 typically means that a function h is being evaluated at the input value of 40, and the output is 1820. This could represent a variety of contexts, such as the height of a rocket in meters at 40 seconds after launch, the amount of money saved after 40 weeks, or any other situation described by a function where the variable h depends on the number 40. Without additional context, it's impossible to say precisely what 1820 refers to, but it is the result of the function h when the input is 40.
rectangle with a side length of 11" and a diagonal of 14" what is the perimeter
Answer:
10sqrt3+22
Step-by-step explanation:
Ok, let us imagine it as a sort of rectangle split upon its diagonal.
Using that, we can Pythag it out,
11^2+b^2=14^2
121+b^2=196
b^2=75
b=sqrt75
b=5sqrt3
Ok, using this info, we find the perimeter,
5sqrt3+5sqrt3+11+11
10sqrt3+22
The answer is 10sqrt3+22
The answer is:
The perimeter of the rectangle is equal to 39.32".
[tex]Perimeter=39.32in[/tex]
Why?Since we are working with a rectangle, we can use the Pythagorean theorem to find the missing side of the rectangle and calculate its perimeter. We must remember that we can divide a rectangle into two equal right triangles.
According to the Pythagorean Theorem, we have:
[tex]a^{2}=b^{2}+c^{2}[/tex]
Where:
a, represents the hypotenuse of the triangle which is equal to the diagonal of the given rectangle (14")
b and c are the other sides of the triangle.
Now, let be "a" 14" and "b" 11"
So, solving we have:
[tex]a^{2}=b^{2}+c^{2}[/tex]
[tex]14^{2}=11^{2}+c^{2}[/tex]
[tex]14^{2}-11^{2}=c^{2}[/tex]
[tex]14^{2}-11^{2}=c^{2}\\\\c=\sqrt{14^{2} -11^{2} }=\sqrt{196-121}=\sqrt{75}=8.66in[/tex]
Now, that we already know the the missing side of the rectangle, we can calculate the perimeter using the following formula:
[tex]Perimeter=2base+2length\\\\Perimeter=2*11in+2*8.66in=22in+17.32in=39.32n[/tex]
Hence, we have that the perimeter of the rectangle is equal to 39.32".
Have a nice day!
classify XYZ.
A. Scalene triangle
B. Right triangle
C. Isosceles triangle
D. Equilateral triangle
Answer:
Scalene Triangle
Step-by-step explanation:
By definition, scalene triangles have 3 sides of unequal length.
FYI,
Right Triangle : triangle with one of the angles = 90°
Isosceles Triangles: Triangle with 2 sides of the same length.
Equilateral triangle: Triangle with 3 sides of the same length.
All rhombuses are. Parallelograms square rectangules quadrilaterals
Step-by-step explanation:
Look at the picture.
All rhombuses are
parallelograms
quadrilaterals
Determine if parallel, perpendicular, or neither.
3y+4x=12
-6y=8x+1
What is the measure of the radius of circle m? see picture
Answer:
10.5 units
Step-by-step explanation:
Since M is the centre of the circle. The measure to the edge is the radius.
Which in this case is 10.5 units
Answer: A. 10.5 units
Step-by-step explanation: The answer would be 10.5 units because the radius is equal to half the circle. MS is a radius, and MR is a radius. A radius has one point in the center, and one point on the circle.
Which equation shows the variable terms isolated on one side and the constant terms isolated on the other side for the equation 3x-5=-2+10
To isolate the variable terms on one side and the constant terms on the other side of the equation 3x - 5 = -2 + 10, add 2 to both sides, simplify to 3x - 3 = 10, then add 3 to both sides to get the final simplified equation 3x = 13.
Explanation:The equation 3x - 5 = -2 + 10 needs to be rearranged to isolate the variable terms on one side and the constant terms on the other. To do this, follow these steps:
Add 2 to both sides to move the constant term from the right to the left side: 3x - 5 + 2 = 10.Simplify both sides: 3x - 3 = 10.Add 3 to both sides to completely isolate the constant terms on one side: 3x = 10 + 3.Simplify the equation: 3x = 13.Now, we have successfully isolated the variable terms (3x) on one side of the equation and the constant terms (13) on the other side.
r=2sec(theta) converted into a cartesian equation
[tex]\bf r=2sec(\theta )\qquad \begin{cases} x=rcos(\theta )\\ \frac{x}{r}=cos(\theta ) \end{cases}\qquad \implies r=2\cdot \cfrac{1}{cos(\theta )}\implies r=\cfrac{2}{~~\frac{x}{r}~~} \\\\\\ r=\cfrac{\frac{2}{1}}{~~\frac{x}{r}~~}\implies r=\cfrac{2r}{x}\implies x=\cfrac{2~~\begin{matrix} r \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}{~~\begin{matrix} r \\[-0.7em]\cline{1-1}\\[-5pt]\end{matrix}~~}\implies x=2[/tex]
Given the system of equations, match the following items.
x + 3y = 5
x - 3y = -1
To solve the system of equations x + 3y = 5 and x - 3y = -1, we add both equations to get 2x = 4, solve for x to find x = 2, and then substitute x back into one of the equations to find y = 1, resulting in the solution (2, 1).
The solution of the system of linear equations given by x + 3y = 5 and x - 3y = -1 involves manipulating the equations to find the values of x and y that satisfy both equations simultaneously. One common method to solve these is to add or subtract the equations, which eliminates one variable, making it possible to solve for the other.
Starting with the addition method, we align the equations and add them together:
x + 3y = 5
x - 3y = -1
Adding these equations, we get 2x = 4, and solving for x gives us x = 2. We can substitute x = 2 back into one of the original equations to find the value of y, yielding y = 1.
The solution to the system is the intersection point of the two lines represented by the equations, which is the point (2, 1).
Simplify the following algebraic expression: 6(2y + 8) - 2(3y - 2)
Answer:
[tex]\large\boxed{6y+52}[/tex]
Step-by-step explanation:
In this question, we're going to simplify the expression.
We would do this by distributing and solving after.
Solve:
[tex]6(2y + 8) - 2(3y - 2)\\\\\text{Distribute the 6 to the 2y and 8}\\\\12y+48- 2(3y - 2)\\\\\text{Distribute the -2 to the 3y and -2}\\\\12y+48-6y+4\\\\\text{Combine like terms}\\\\6y+48+4\\\\\boxed{6y+52}[/tex]
When you're done solving, you should get 6y+52
This means that the simplified version would be 6y+52
I hope this helped you out.Good luck on your academics.Have a fantastic day!Which numbers are irrational? Check all that apply
Irrational numbers cannot be expressed as a fraction or ratio of two integers and have decimal representations that go on forever without repeating.
Explanation:Irrational numbers are numbers that cannot be expressed as a fraction or ratio of two integers. They are decimal numbers that go on forever without repeating. Examples of irrational numbers include π, √2, and √3. These numbers cannot be expressed as a simple fraction or as a terminating or repeating decimal.
What is the solution to the system of equations graphed below?
А.(6, 0)
B.(1, 5)
С.(0.3)
D.(0,6)
Answer:
B
Step-by-step explanation:
The solution to a system of equations given graphically is at the point of intersection of the 2 lines, that is
Solution = (1, 5 ) → B
[tex]\huge{\boxed{\text{(1, 5)}}}[/tex]
All you need to do is find where the intersection of the lines is located.
Count how many units to the right. [tex]1[/tex] This is our [tex]x[/tex] value.
Count how many units up. [tex]5[/tex] This is our [tex]y[/tex] value.
Please help me, I Am getting-28 but I do t think it is correct
Answer:
-28
Step-by-step explanation:
[tex]-(2-2^3)^2-4 \cdot (-2)[/tex]
We going to use PE(MD)(AS).
So P means ( ).
We do have operations to perform in the ( ).
We have [tex]2-2^3[/tex] in the first set of ( ) and (-2) in the second set of ( ).
There are no operations in the second set containing -2.
So we are just focusing on the [tex]2-2^3[/tex] right now.
You have subtract and exponent here.
Exponents come first in PE(MD)(AS) so we will perform that first.
[tex]2-2^3=2-8=-6[/tex]
Let's go back to the original problem now.
[tex]-(2-2^3)^2-4 \cdot (-2)[/tex]
[tex]-(-6)^2-4 \cdot(-2)[/tex]
Now there are no longer any operations grouped together by use of ( ).
It on to the rest of PE(MD)(AS).
So now we are doing the E part, the exponents.
[tex]-(36)-4 \cdot(-2)[/tex]
Now there is multiplication and subtraction left.
(MD) comes before (AS) so we do the multiplication and then the subtraction. So I'm going to do 4(-2) now:
[tex]-(36)-(-8)[/tex]
Subtraction is addition of the opposite so you could write:
[tex]-(36)+8[/tex]
We don't really need ( ) around the first number:
[tex]-36+8[/tex]
36-8 is 28 but since 36>8 and 36 has a negative sign on it, the answer is -28.
Solve for x. Write the smaller solution first, and the larger solution second. (x-10)^2-1=0
Answer:
[tex]x_1 = 9[/tex] and [tex]x_2 = 11[/tex].
Step-by-step explanation:
Start by adding 1 to both sides of this equation.
[tex](x - 10)^{2} = 1[/tex].
The square of what number or numbers will lead to the number "1"? It turns out that not only [tex]1^{2} = 1[/tex], but [tex](-1)^{2}= 1[/tex] as well. In other words, the value [tex](x - 10)[/tex] can be either 1 or -1. Either way, the equation is still going to hold. That's the reason why there are two solutions to this equation.
Consider the case when [tex]x - 10 = 1[/tex]. Add 10 to both sides of the equation. [tex]x = 11[/tex].
Now, consider the case when [tex]x - 10 = -1[/tex]. Again, add 10 to both sides of the equation, [tex]x = 9[/tex].
Order the two solutions in an increasing order:
[tex]x_1 = 9[/tex],[tex]x_2 = 11[/tex].